If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 2 = -3 + -12 Reorder the terms: 2 + 4x = -3 + -12 Combine like terms: -3 + -12 = -15 2 + 4x = -15 Solving 2 + 4x = -15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 4x = -15 + -2 Combine like terms: 2 + -2 = 0 0 + 4x = -15 + -2 4x = -15 + -2 Combine like terms: -15 + -2 = -17 4x = -17 Divide each side by '4'. x = -4.25 Simplifying x = -4.25
| 6x^2+108x+486=0 | | y=2x^2-5x+2 | | 3*(x-5)+4(1-2x)=-3 | | 4.2x-1.2y=2.1 | | 2x+5=13[-5] | | 9x^2+0.6x=0 | | 9x^2=-0.6x | | 9x^2-0.6x=0 | | 1.8+2.2h+3.7=-2.5-1.8h+.5 | | (4z-5)(3z-2)-(3z-9)(3z-2)= | | 4x^2+y^2-4xy=4 | | 3+3x+5=17 | | (x-2)*(x+2)=21 | | x^3-12x^2+5x-300=0 | | sin(x)=0.5 | | x^2-30x+10=0 | | 2x-3=27 | | 3(6m-2)=5m+2(7m+5) | | 2x+6=8x+3 | | c+8=12 | | x+9=4x-28 | | 8x+5=27 | | 10x-13=4x+23 | | -8(4-2n)=6(n+3) | | 7/2+3/2*-9=-9+1.5*9 | | 8x+5=85 | | 3x+1.3=-4x+0.7 | | -5p-2p=7(4p+4)+6(3-2p) | | 5a^2-15= | | -6a=40a | | -2b-1+8b=3(7b-7)+5(-2b+6) | | 4a+(2b-3a)= |